The Relationship Between Dental Students' Assessment Ability and Preclinical and Academic Performance in Operative Dentistry. Issue 3 (1st March 2017) - Lee, Cliff; Asher, Sheetal R.; Chutinan, Supattriya; Gallucci, German O.; Ohyama, Hiroe
Abstract : Self‐assessment is a critical skill for health care professionals. Because these professionals must be lifelong, self‐directed learners and self‐regulating practitioners, the ability to self‐assess is essential for them. The aims of this study were to measure how dental students self‐assessed and peer‐assessed their performance in preclinical operative procedures and to evaluate any relationship between their assessment ability and preclinical skills or academic performance. The study was conducted from 2015 to 2016. Third‐year students at Harvard School of Dental Medicine self‐assessed their work on four preclinical practical exams: Class II amalgam preparation, Class II amalgam restoration, Class III composite preparation, and Class III composite restoration. Three faculty members graded the same preparations and restorations. The difference between the students' self‐assessment and the mean faculty assessment was calculated as the student‐faculty (S‐F) gap. An absolute S‐F gap was also calculated with absolute values of differences. A total of 71 students completed these practical exams: 36 in the Class of 2016 and 35 in the Class of 2017. All 71 self‐assessments for each of the four practical exams were collected for a response rate of 100%. The results showed that the mean S‐F gap ranged from 2% to 8%, and the absolute S‐F gap ranged from 7% to 12%. Preclinical performance was correlated with self‐assessment accuracy. Low‐performing students significantly overestimated their self‐assessments compared to the rest of the class. High‐performing students had more accurate self‐assessments and tended to underestimate themselves. Overall, these results showed that the students had room for improving the accuracy of their self‐assessments.